Alu Mobile Elements: From Junk DNA to Genomic Gems - Sami Dridi (Scientifica)
Alus, the short interspersed repeated sequences (SINEs), are retrotransposons that litter the human genomes and have long been considered junk DNA. However, recent findings that these mobile elements are transcribed, both as distinct RNA polymerase III transcripts and as a part of RNA polymerase II transcripts, suggest biological functions and refute the notion that Alus are biologically unimportant. Indeed, Alu RNAs have been shown to control mRNA processing at several levels, to have complex regulatory functions such as transcriptional repression and modulating alternative splicing and to cause a host of human genetic diseases. Alu RNAs embedded in Pol II transcripts can promote evolution and proteome diversity, which further indicates that these mobile retroelements are in fact genomic gems rather than genomic junks.